Transcultural adaptation of the Trinity Amputation and Prosthesis Experience Scales - Revised (TAPES-R): evaluation of psychosocial processes involved in adjustment to amputation and prosthesis - Matos, Denise Regina; Naves, Juliana Fákir; Araujo, Tereza Cristina Cavalcanti Ferreira de (Acta Fisiátrica, 2018)
The literature indicates the absence of specific instruments for clinical evaluation and research directed at people with amputation, with the TAPES-R scale being relevant for the analysis of psychosocial aspects in this population. This scale was developed to evaluate the processes involved in adapting to lower limb amputation and to the prosthesis. This instrument covers 33 items organized in three domains - psychosocial adjustment, activity restriction and prosthesis satisfaction, as well as issues related to phantom limb and residual limb pain. Objective: To perform transcultural adaptation of the TAPES-R scale for application in the Brazilian population. Method: Transcultural adaptation was carried out in five stages: translation, reverse translation, synthesis of the evaluations, evaluation by expert committee and final test in the population. The comparison between the original and translated versions was performed in relation to the semantic, idiomatic, cultural and conceptual equivalences. The final version was applied to 116 amputees of the lower limbs. Results: There was clarity regarding participants' understanding of the instrument, indicating that it is appropriate to the reality of the target audience in the Brazilian population. Amputation above the knee and time of use of the prosthesis below 10 hours / day are associated with worse fit and less satisfaction with the prosthesis. Conclusion: The use of the TAPES-R scale allowed the evaluation of the individuals' perception about the experience with the amputation and prosthesis, allowing the clinical use to evaluate the results for the rehabilitation of patients with lower limb amputation. Further studies will be developed for the continued validation of the instrument.